One‐Step Construction of Novel PbBiO2Br/ZnO Heterojunction Composites with Enhanced Photocatalytic Activity. Issue 20 (22nd August 2019) - Xia, Yongmei; He, Zuming; Su, Jiangbin; Li, Xiaoping; Tang, Bin
Abstract : PbBiO2 Br/ZnO heterojunction composites are synthesized using a one‐step method. The as‐synthesized samples are characterized by X‐ray diffraction (XRD), X‐ray photoelectron spectroscopy (XPS), field‐emission scanning electron microscopy (FE‐SEM), energy‐disperse X‐ray spectroscopy (EDX), transmission electron microscopy (TEM), Fourier‐transform infrared spectroscopy (FTIR), Brunauer–Emmett–Teller (BET), ultraviolet‐visible diffuse reflectance spectroscopy (UV‐vis DRS), and photoluminescence (PL) spectroscopy. The photocatalytic activity of the PbBiO2 Br/ZnO heterojunction composites is assessed by measuring the removal of methyl orange (MO) from wastewater under simulated sunlight irradiation. The results demonstrate that the PbBiO2 Br/ZnO heterojunction composites are composed of ZnO nanorods and PbBiO2Br cubic nanosheets. The PbBiO2 Br/ZnO heterojunction composites exhibit enhanced photocatalytic performances for the degradation of MO under irradiation by simulated sunlight. Among the composites, the 10% PbBiO2 Br/ZnO composite exhibits optimal activity, and the removal percentage of the dye reaches 92.1% after 60 min of reaction. This is mainly attributed to the efficient separation of photo‐generated e − –h + pairs and the formation of heterojunctions. According to the active species trapping experiments, photo‐generated h + is confirmed to be the main active species, whereas · O 2 − and · O H play a secondary role in the reaction process. Additionally, the recycling experiments suggest that the PbBiO2 Br/ZnO composites have good stability in the reaction process. Abstract : Novel PbBiO2 Br/ZnO composites are successfully fabricated by a one‐step method. Among the composites, the 10% PbBiO2 Br/ZnO composite exhibits the optimal photocatalytic activity. PbBiO2 Br can effectively separate the photo‐induced electron‐hole pairs. At the same time, hole is confirmed to be the main active species, whereas · O 2 − and · O H play a secondary role in the reaction process.